Pengaruh Kemudahan, Kemanfaatan, Risiko, dan Keamanan Terhadap Keputusan Penggunaan QRIS Pada Generasi Muslim Muda Soloraya - Azmi, Deva Desinta Nur; Budiarti, Yulia (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2024)
Digital payments are growing rapidly in Indonesia, one of which is payment via QRIS (Quick Response Code Indonesian Standard). This payment is a unification of various QR Codes that exist in payment system service providers or PJSP. This non-cash or cashless payment with QRIS has become a trend for the younger generation because it is practical and effective. This research was conducted to analyze perceived ease of use, perceived usefulness, perceived risk, and perceived security, which influence the decision to use QRIS in the young Muslim generation in Soloraya. The research method uses quantitative primary data, with a descriptive approach. 105 respondents from the young Muslim generation in Soloraya who have used QRIS, the sample used is non-probability sampling. The data were analyzed statistically using IBM SPSS Statistics 25 software. In this study, the TAM theory was used to approach the digital payment system via the QR Code, namely the Quick response code Indonesian standard (QRIS). The results showed that there was a simultaneous and partially significant effect on the perceived ease, benefit, risk, and security variables on the decision to use QRIS in the young Muslim generation in Soloraya.